2016
DOI: 10.1080/10618600.2015.1054033
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Flexible ADMM Algorithms for Trend Filtering

Abstract: This paper presents a fast and robust algorithm for trend filtering, a recently developed nonparametric regression tool. It has been shown that, for estimating functions whose derivatives are of bounded variation, trend filtering achieves the minimax optimal error rate, while other popular methods like smoothing splines and kernels do not. Standing in the way of a more widespread practical adoption, however, is a lack of scalable and numerically stable algorithms for fitting trend filtering estimates. This pap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
115
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(115 citation statements)
references
References 20 publications
0
115
0
Order By: Relevance
“…Piecewise linear fits are better-suited to this type of relationship. The problem of estimating piecewise trends of any order between a single predictor and response has been previously explored [Kim et al, 2009, Ramdas and Tibshirani, 2014, Tibshirani, 2014]. We leave the extension of FLAM to this setting to future work.…”
Section: Discussionmentioning
confidence: 99%
“…Piecewise linear fits are better-suited to this type of relationship. The problem of estimating piecewise trends of any order between a single predictor and response has been previously explored [Kim et al, 2009, Ramdas and Tibshirani, 2014, Tibshirani, 2014]. We leave the extension of FLAM to this setting to future work.…”
Section: Discussionmentioning
confidence: 99%
“…Using Bowtie (Langmead et al 2009) default parameters, 5 ′ -and 3 ′ -end reads were aligned to corresponding genomes and converted to single nucleotide read-end pileups. To identify significant read peaks, we simultaneously inferred the size and locations of constant backgrounds using first-order Poisson trend filtering with outlier detection as described (Ramdas and Tibshirani 2016;Supplemental Methods). RNA-seq and Ribo-seq library preparation was performed as previously described (McManus et al 2014;Spealman et al 2016), except that S. uvarum libraries were produced using the ART-seq kit (Illumina) (for full details, see Supplemental Materials).…”
Section: Methodsmentioning
confidence: 99%
“…However, the authors claim that in practice the interior-point method converges in tens of iterations, in which case the general running time for solving the optimization problem will still be O ( N ). The other specialized optimization method for trend filtering problem is recently proposed by A. Ramdas et al [28]. They introduced a specialized alternating direction method of multipliers (ADMM), and they showed that their method has better scalability and faster convergence rate for large scale problems compared to the interior-point based method, while on the small sample sizes they have similar performance to the interior-point based method proposed by Kim et al [22].…”
Section: Methodsmentioning
confidence: 99%
“…The resulting optimization program will be equivalent to the recently proposed ℓ 1 trend filtering signal approximation method [22]. It uses recently proposed alternating direction method of multipliers (ADMM) based optimization method to find a collection of a piecewise linear calibration mappings [28]. Finally, it uses the AICc scoring measure [5] to combine the predictions made by these models to yield more robust calibrated predictions for each of the test instances.…”
Section: Related Workmentioning
confidence: 99%